Knowledge Development of the Beard Community through Socialization of Community Empowerment of Toga, Chili and Eggplant Plants - ‘Aisy , Qatrunnada Salsabila Rohadatul; Abror, M. (Indonesian Journal of Cultural and Community Development, 2025)
The community service program in Jenggot Village, Krembung District, Sidoarjo Regency, aims to improve the welfare of village communities through empowering family medicinal plants (TOGA), chili and eggplant. This program is implemented with the KKN-T scheme and the theme "Collaboration with the Community for Progressive Villages and Branches". Jenggot Village faces challenges in overcoming pests and diseases in Family Medicinal Plants (TOGA) as well as chili and eggplant plants which often reduce harvest yields. The methods used included observation, outreach, and giving away 400 chili and eggplant seeds for free. As a result, the people of Jenggot village gained understanding and insight into the empowerment of family medicinal plants, chili and eggplant, and were able to overcome the challenges they faced in dealing with pests and diseases in plants